Online Student Satisfaction in Following Distance Learning Using the Microsoft Teams Application - Afif, Muhammad; Azhar, Muhammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this research is to find out whether students are able to take part in distance learning properly according to their expectations or not so that they feel satisfaction in learning online using Microsoft Teams. This type of research is descriptive and quantitative. The total population is 135 Bintang Pelajar class 12 high school students who take part in assistance to enter public universities. The sampling method was convenience sampling, with a total sample size of 131 respondents. Data collection techniques include surveys and filling out questionnaires. Data analysis was carried out by presenting quantitative data in the form of numbers and graphics and then describing the conditions of the subjects. The result is that 54.20% of respondents are very satisfied and can follow the lesson very well; 41.98% are satisfied and can follow well; and 3.82% are dissatisfied and are unable to follow because it is too fast or unclear.